Quality Assurance Practices in Distance Learning Institute of University of Lagos, Nigeria - Iyiegbuniwe, Joy Chimebere; Alaneme, Gloria Chinyere (West African Journal of Open and Flexible Learning, 2026)
The purpose of this study is to critically assess the quality of the programmes of Distance Learning Institute of University of Lagos, Nigeria. This was achieved through a survey of a sample of 300 students drawn using a simple random sampling method, out of 2,233 final-year students. The instrument is a self-completion questionnaire. The variables were tested for statistical significance with two-failed t-lest at p values of 0,01 and 0,05. It was found that the quality of staff and lecture delivery; access to admission; curriculum and instruction were satisfactory. However, there were mixed feelings on students' orientation; student counselling; coverage of the syllabus before examinations, and learning resources. It is therefore recommended that the institution should improve on the areas where there are mixed feelings.
Keywords: Quality assurance; curriculum and instruction; faculty support; access; faculty satisfaction and student satisfaction